Development of a gap searching program for automotive body assemblies based on a decomposition model representation. (March 2015) - Yun, Jaedeuk; Lee, Sunghoon; Jung, Yoongho
Highlights: We suggest a method of locating gaps between the parts of an assembly automatically. We propose an algorithm to define the boundary between the exterior and the gaps. The developed program can visualize gaps of less than 1 mm in a specified region. It can help to avoid design changes and repair processes while developing products. Application of the method can also be extended to aircraft and ship designs. Abstract: Automobiles, aircraft, and ships require tremendously many parts to be assembled. For developing such large assemblies, most companies accelerate the design process by having many design engineers in different functional or sectional design groups working concurrently. However, interferences and gaps can be found when the parts and sub-assemblies of different design groups are to be assembled. These error cause design changes and additional repair processes, resulting in an unexpected increase in costs and time delays. While the interference problem has been resolved by digital mockup and concurrent engineering methodology, many cases of the gap problem in the automotive industry have been covered by temporary treatments when the gaps are small enough to be filled with sealants. This kind of fast fix can cause leakage into the engine chamber and passenger cabin when the gap size is too big for filling or when the sealant gets old, which can turn fatal. With this research, we have developed a program to automatically find gaps between the parts of an assembly so that design engineers can correct their designs before the manufacturing stage begins. By using the method of decomposition model representation, the program can visualize gaps between complex car body parts as well as estimate their volumetric information. It can also automatically define the boundary between a gap and the exterior space. Although we have reviewed the benefits of the program by applying it to car development, it can also be applied to aircraft and ship designs comprising several parts.